Стратегічні можливості підприємства та їх оцінювання - Коваль, З. О.; Koval, Z. O. (Видавництво Львівської політехніки, 2023)
Запропоновано методику оцінювання стратегічних можливостей підприємств за допомогою застосування теорії ймовірності, що дасть змогу врахувати і параметри їх внутрішнього середовища, що визначають ефективність обраної стратегії, і особливості зовнішнього середовища, що у складних умовах сьогодення характеризується значним рівнем нестабільності і непередбачуваності. Розглянуто переваги і недоліки застосування цієї методики під час розроблення, вибору та оцінювання стратегій підприємств, розглянуто особливості застосування її у визначених ситуаціях, досліджено ймовірність реалізації підприємством свої можливостей за різних типів визначеності та змінності зовнішнього середовища, що сприятиме підвищенню об’єктивності оцінки розриву між стратегічними цілями підприємств та їх можливостями та допоможе виявити напрями скорочення цього розриву у довготерміновій перспективі.

Assessment of strategic opportunities is an important stage of strategic planning for the development of an enterprise and an important component of its strategic management system. The study of the strategic level of the enterprise, its strategic potential will make it possible to analyze the features and determine the prospects of its development for the future. The evaluation of the level of effectiveness of the strategy chosen by the enterprise, which characterizes the direction of its strategic development, will allow to effectively influence the current state of economic activity and the dynamics of changes in this state, to identify more important factors that caused the specified changes, to forecast and plan such changes. A characteristic of strategic development in the process of such an assessment is the company’s ability to achieve strategic goals and planned strategic results of its activities during the planned time period. At the same time, the availability and efficiency of the use of the appropriate resources necessary for the implementation of the strategy, the ability to adapt the strategy to changes occurring under the influence of internal and external environmental factors, as well as the ability to obtain significant competitive advantages due to the choice of the appropriate strategy, etc., also become important. The results of the analysis of these and other parameters specified in the study indicate the strategic capabilities of the enterprise, that is, its ability to take advantage of the positive influence of external factors for its development and counteract the influence of negative factors, or minimize their influence on its activities. The article proposes a methodology for assessing the strategic capabilities of enterprises using the theory of probability, which will make it possible to take into account both the parameters of their internal environment, which determine the effectiveness of the chosen strategy, and the features of the external environment, which in today’s complex conditions is characterized by a significant level of instability and unpredictability. The advantages and disadvantages of using this method during the development, selection and evaluation of enterprise strategies are considered, the peculiarities of its application in certain situations are considered, the probability of the enterprise realizing its opportunities under various types of certainty and variability of the external environment is investigated, which will contribute to increasing the objectivity of assessing the gap between strategic the goals of enterprises and their capabilities and will help identify directions for reducing this gap in the long-term perspective.
Strategic opportunities of the enterprise and their assessment
Keywords: стратегічні можливості підприємства; стратегія; оцінювання ефективності стратегії; теорія ймовірності; strategic capabilities of the enterprise; strategy; evaluation of strategy effectiveness; theory of probability; 338.33; 658